Forecaster - Coasters Association (2008)
Number of pages: 4

Kids Summer Camp - Newcombe, Vanessa (Coasters Association, 2008)
The KIDS Summer Camp has been in operation since 2006 and has provided a summer retreat for over 200 youth in five (5) communities, (Blanc Sablon, St. Paul’s River, St. Augustine, La Tabatiere as well as the Eau-Naturelle Discovery Camp in Chevery) thus, accommodating the youth and parents in the five (5) municipalities across the Lower North Shore. Furthermore it provides a vital service to the parents who have no other option but leave the coast for 3 to 4 months out of a year to seek employment elsewhere.

French Immersion Teen Camp : Feasibility Study - Newcombe, Vanessa; Roberts, Carla; Griffin, Emily (Coasters Association, 2008)
Living in such an isolated area such as, the Lower North Shore, there is a lack of activities for all ages, but more so for the adolescent age. There are very few activities on the Lower North Shore that directly focuses on teenagers, so teens resort to other activities that result in social problems (i.e. drinking, drugs, vandalism, etc…). Therefore, a French Immersion Teen Camp would provide teenagers with activities and a program that is especially designed for them. Teenagers could have a chance to get away from the social problems and into a program that will nurture and develop a safe and healthy environment in which the teens can improve their health and obtain skills that will assist them in their future lives and also promote and develop their French as a Second Language skill.

2008 Youth Consultation on the Lower North Shore - Buckle, Heidi (Coasters Association, 2008)
The 2008 Lower North Shore Youth Consultation was coordinated to provide a needs assessment of the English-speaking youth on the coast, addressing topics related to youth retention and youth out migration. The projected outcome of the consultation was to empower youth with a collective identity and to encourage greater participation within the Lower North Shore at large.

"A Matter of Services - Addressing the Health Issues" : October 2004 to March 2008 - Jones, Ida (Coasters Association, 2008)
The Coasters Association Inc. received a project from Health Canada entitled, “A matter of Services - Addressing the Health Issues” through the Quebec Community Group Network partners. The HSSNPI started on October 18th, 2004. In the first phase, we have accomplished the establishment of a networking committee called the Lower North Shore Coalition for Health (LNSCH). This committee steers the HSSNPI program and approves the data evidence plans generated. Surveys were created and focus groups held on topics (youth and children, women’s issues, wait times and post care, transportation and lodging, and drugs and alcohol) to determine the Health and Social Service needs of the population, this information was instrumental in the planning for the second phase. A synopsis of the current actions and history of the organizations involved in the LNSCH was completed. The mission of the project is to support the development of the capacity of Quebec’s English-speaking communities, to ensure their vitality through cooperation and partnership with the health and social services system, in order to improve and to develop and maintain access to the full range of services for Quebec’s English - speaking minority communities.